2005
DOI: 10.1021/ja043470s
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Enolization of β-Amino Carboxamides by Lithium Hexamethyldisilazide

Abstract: The enolization of beta-amino carboxamides by lithium hexamethyldisilazide (LiHMDS) in THF/toluene and subsequent diastereoselective alkylation with CH(3)I are reported. In situ IR spectroscopic studies reveal that beta-amino carboxamides coordinate to LiHMDS at -78 degrees C before enolization. Comparison with structurally similar carboxamides suggests that the beta-amino group promotes the enolization. IR spectroscopic studies also show that the enolization is reversible. Efficient trapping of the enolate by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…K-VI!1/2 K-VII À11.28 17 1/2 K-II + TMEDA!1/2 K-VII À10.09 18 K-I + TMEDA!1/2 K-VII À25.25 19 1/3 K-III + TMEDA!K-VI + 2.66 20 1/3 K-III + TMEDA!1/2 K-VII À8.62 21 1/3 K-III + 2 TMEDA!K-VIII À6. 19 22 K-VIII!1/2 K-VII + TMEDA À2.…”
Section: Synthesis Of [{(Tmeda)mentioning
confidence: 99%
See 1 more Smart Citation
“…K-VI!1/2 K-VII À11.28 17 1/2 K-II + TMEDA!1/2 K-VII À10.09 18 K-I + TMEDA!1/2 K-VII À25.25 19 1/3 K-III + TMEDA!K-VI + 2.66 20 1/3 K-III + TMEDA!1/2 K-VII À8.62 21 1/3 K-III + 2 TMEDA!K-VIII À6. 19 22 K-VIII!1/2 K-VII + TMEDA À2.…”
Section: Synthesis Of [{(Tmeda)mentioning
confidence: 99%
“…There are numerous accounts of alkalimetal amides being used to achieve alkali-metal/hydrogen exchange, and the use of alkali-metal amides (in particular those of lithium) has been well reviewed. [8,[12][13][14][15] More specifically, the amides have been used recently in certain transformations such as the generation of enolates, [16][17][18][19][20][21][22][23][24][25] condensation and ring-formation processes, [26][27][28] directed ortho-metalations (DoM), [29][30][31][32][33][34][35][36][37][38][39] rearrangement and isomerization processes, [40][41][42][43][44] and in Wittig reactions. [45][46][47][48] From a structural perspective, the chemistry of the alkali metal amides has been the focus of a great deal of attention, both in solution and in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…Since lithium, sodium and potassium HMDS reagents are commercially available, they have become prominent transfer reagents for the synthesis of s-block metal, 4 transition metal, [5][6][7] lanthanide 8 and actinide 9,10 HMDS complexes via salt metathesis. In synthesis, they are used in a wide variety of chemical transformations ranging from drug synthesis to polymer pro-duction, such as in the formation of kinetic enolate anions, [11][12][13] alkylations, 14 arylations, 15 isomerisations, 16 polymerizations, 17 ring closing reactions and Wittig reactions, 18,19 and also, in the deprotonative metallation of acidic C-H bonds, like cyclopentadiene, indene and fluorene. [20][21][22] Most recently, several organic transformations have been reported which use alkali metal HMDS salt complexes in combination with a Lewis basic donor molecule to induce catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…showed a band at 1591 cm -1 . This absorption is characteristic of the C=C band of an enolate, [31] and suggested that rapid conversion of 2a into enolate I takes place (Figure 2). When the reaction was monitored for longer periods of time, this absorption band slowly disappeared (see the Supporting Information, Figure SI1).…”
Section: Resultsmentioning
confidence: 98%